Contractor's Responsibility for a Work Contract in a Project Direct Appointment by the Commitment Making Officer (PPK) of the Regional Government Organization (OPD) (Study at the Public Works and Spatial Planning Department of Tanjungbalai City) - Zuhdi, Muhammad Aufa; Siregar, Emiel Salim (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The Reformation era was an era of change in national and state life. The reform era began in 1998. The background to the birth of the Reform Era was the dysfunction of the wheels of government in national and state life, especially in the fields of politics, economics and law. So with the Reformation, state administrators want to make radical (fundamental) changes in these three areas. The form of contractor responsibility for a work contract in a Direct Appointment project, where basically the responsibility of the contractor (work implementer) in the work contract in all selection models (whether direct appointment or not) is the same. The cooperation contract system and payment method with contractors and terms and each month which is influenced by the form of contract for the Direct Appointment method is in the form of a Letter of Agreement. Meanwhile, the type of contract can be a Laumpsum Contract, or a Unit Price Contract, or a Combined Unit Price and Laumpsum Contract. Usually using a Combined Unit Price and Laumpsum Contract. Except for emergency work using unit price contracts. Meanwhile, the method or method of payment can be termly or monthly (certificate mountly: based on work performance). The formulation of the problem discussed is how the contractor's responsibilities regarding work contracts in projects are directly appointed by the PPK of the Tanjungbalai City Public Works and Spatial Planning Service